2022
DOI: 10.1007/s00415-022-11479-z
|View full text |Cite|
|
Sign up to set email alerts
|

Resting-state functional MRI in multicenter studies on multiple sclerosis: a report on raw data quality and functional connectivity features from the Italian Neuroimaging Network Initiative

Abstract: The Italian Neuroimaging Network Initiative (INNI) is an expanding repository of brain MRI data from multiple sclerosis (MS) patients recruited at four Italian MRI research sites. We describe the raw data quality of resting-state functional MRI (RS-fMRI) time-series in INNI and the inter-site variability in functional connectivity (FC) features after unified automated data preprocessing. MRI datasets from 489 MS patients and 246 healthy control (HC) subjects were retrieved from the INNI database. Raw data qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“… ReHo mean difference calculated with each scanner's fMRI were 0.0039, 0.0005, −0.0007 and −0.01 for Siemens Skyra Fit, Philips Elition X, GE Premier, and Siemens Vida, respectively. The variability of ReHo values as a function of functional time points has also been reported in previous studies [ 49 ] and explains why ReHo values in present study for Siemens Skyra (time points = 200) was less as compared to other scanners (time points = 380). ALFF values showed significantly larger variations amongst all the scanners with ALFF mean of 476, 210,304, 1480, 41.76 for Siemens Skyra Fit, Philips Elition X, GE Premier and Siemens Vida respectively.…”
Section: Protocol Validationsupporting
confidence: 86%
“… ReHo mean difference calculated with each scanner's fMRI were 0.0039, 0.0005, −0.0007 and −0.01 for Siemens Skyra Fit, Philips Elition X, GE Premier, and Siemens Vida, respectively. The variability of ReHo values as a function of functional time points has also been reported in previous studies [ 49 ] and explains why ReHo values in present study for Siemens Skyra (time points = 200) was less as compared to other scanners (time points = 380). ALFF values showed significantly larger variations amongst all the scanners with ALFF mean of 476, 210,304, 1480, 41.76 for Siemens Skyra Fit, Philips Elition X, GE Premier and Siemens Vida respectively.…”
Section: Protocol Validationsupporting
confidence: 86%
“…After RS fMRI pre-processing (Supplementary methods), TVFC was assessed basing on the calculation of degree centrality, 26 a measure quantifying the relative importance of individual gray matter (GM) voxels over the whole-brain networks that was already used in multicenter studies of MS 26 and showed minor scanner-related effects, easy to be controlled using scanner-adjusted statistical models. 27 Using DPABI software (http://rfmri.org/dpabi), we splitted RS fMRI scans into sliding windows of 22 time points (Scanner 1) or 42 time points (Scanner 2), to take into account for different repetition times/acquisition lengths (but at the same time maintaining an equal window length in seconds across scanners), with a shift length of one volume across windows. Degree centrality maps were computed for each window.…”
Section: Methodsmentioning
confidence: 99%
“…MRI data were preprocessed using a fully automated pipeline specifically assembled for the serial extraction of FC features from rs‐fMRI data acquired in large samples of subjects including MS patients (De Rosa et al, 2023 ). In detail, brain tissue segmentation was performed with FreeSurfer v7.1.1 (Fischl, 2012 ), employing 3D T1w and co‐registered FLAIR scans with the sequence adaptive multimodal segmentation (SAMSEG) (Cerri et al, 2021 ) procedure to automatically and simultaneously perform whole‐brain tissue segmentation, including white matter (WM), gray matter, cerebrospinal fluid (CSF) volumes, and MS lesion segmentation for lesion load (LL) estimation.…”
Section: Methodsmentioning
confidence: 99%